Peran Komunikasi Interpersonal Guru Dalam Meningkatkan Percaya Diri Siswa di Pondok Pesantren Nurul Iman Dalam Perspektif Siswa - Nurfadhilah, Annisa; Kamalludin , Kamalludin; Milla , Sri Nurul (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Pahlawan Tuanku Tambusai, 2023)
In essence, humans need communication in dealing with other people. Interpersonal communication is the process of delivering information or messages from someone or using people to someone or a group of other people which is an interpersonal interaction that is a symbolic system, linguistics, such as verbal and non-verbal systems. This system can be socialized directly / face to face or through other media. Basic Human Personality and is a set of basic human potentials that contain the power to do something better and is a blend of intellectual and spiritual knowledge. In that sense, not only smart in education but further than that mastery of the soul or spiritual so that it will form students who have independent, disciplined, honest, responsible, creative, innovative and noblecharacter. Then the main problem is how interpersonal communication in shaping the character of students and the role of caregiver Interpersonal Communication in educating students in religious knowledge and general education. This research is a research, which is a research carried out by lifting the data in the field that is needed, namely data from the Nurul Iman Al-Hasanah Islamic Boarding School. The data collection method used is interviews as primary data, while other methods used are observation and documentation.